The Dominance of Leadership Style, Organisational Culture, and Compensation on Employee Performance at PT. United Motors Centre Surabaya - Ika Amelia Rosanti; Bisma Arianto*; Bayu Akbar Harmono; Fitri Anggraini Hariyanto (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to determine how leadership style, organisational culture, and compensation impact on employee performance PT. United Motors Centre Surabaya. A quantitative-based method was used, the research sample consisted of 67 people selected randomly and based on probability. Likert scale was used to collect data through questionnaires. Before data analysis was conducted, validity, reliability, and classical assumptions were tested using SPSS 26. The result showed that leadership style had no direct impact on employee performance. In contrast, organisational culture and compensation have a direct impact on employee performance.